1993
DOI: 10.1111/j.1365-2788.1993.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cytogenetic survey of institutionalized mentally retarded patients with emphasis on the fragile‐X syndrome

Abstract: A detailed clinical and cytogenetic survey for the fragile-X syndrome was undertaken on 201 institutionalized mentally retarded males with no previously recognized cause of retardation, and the causes of mental retardation were summarized from a total of 595 institutionalized male and female patients after the review of their medical records including clinical and cytogenetic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…For example, Butler and Singh [9] reported 2.0% fragile X positive in his cases, while in our study it was 3.8%. Nevertheless, our results indicate that the diagnostic contribution of the fragile X screening could be considered equally important as conventional chromosome banding techniques for the detection of structural chromosome abnormalities.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…For example, Butler and Singh [9] reported 2.0% fragile X positive in his cases, while in our study it was 3.8%. Nevertheless, our results indicate that the diagnostic contribution of the fragile X screening could be considered equally important as conventional chromosome banding techniques for the detection of structural chromosome abnormalities.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the percentage of chromosome aberrations found in patients with non specific mental retardation was 2.2% [8]. A study done by Butler and Singh [9] in America showed that 39 out of 201 (6.6%) institutionalized MR patients had abnormal chromosome with Down’s syndrome noted in 31 of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A cytogenetic and clinical survey of 236 mentally retarded males (39 with and 197 without the fra(X) syndrome or other recognizable cause of their retardation) was undertaken recently including a comprehensive assessment of anthropometric variables, and significant differences were reported for 18 measurements (weight, height, 7 linear, 2 breadth, 5 craniofacial, 1 skinfold and testicular volume) (Butler et al 1991a, Butler & Singh 1993 …”
Section: Methodsmentioning
confidence: 99%
“…A cytogenetic and clinical survey of 236 mentally retarded males (39 with and 197 without the fra(X) syndrome or other recognizable cause of their retardation) was undertaken recently including a comprehensive assessment of anthropometric variables, and significant differences were reported for 18 measurements (weight, height, 7 linear, 2 breadth, 5 craniofacial, 1 skinfold and testicular volume) (Butler et al 1991a, Butler & Singh 1993. A subset of these individuals was used in the current study to compare anthropometric and craniofacial profile patterns between mentally retarded males with and without the fra(X) syndrome and, in addition, affected males with either high or low fra(X) chromosome expression.…”
Section: Methodsmentioning
confidence: 99%
“…There is a slight male preponderance (1.3–1) (5) and it is three times more prevalent in the Asian community (6). The causes of learning disability are numerous and can be attributed to either genetic or environmental factors affecting neurodevelopment [see Table 2 (7–9)]; 40–80% of children with a learning disability have no identifiable cause (7,10,11). The commonest identifiable cause is a chromosomal aberration particularly in children with severe learning difficulties although 19% of children with mild learning difficulties also do (12).…”
Section: Introductionmentioning
confidence: 99%